+0  
 
0
75
1
avatar

Given that f(x) is a function such that f(1)=2 ,f(4)=3 ,f(7)=4 , and \(f^{-1}(x)\) is the inverse of f(x), what is \(f^{-1}(f^{-1}(3))\)?

 Dec 19, 2019
 #1
avatar+109563 
+1

The points   ( 1, 2)  ,  ( 4, 3)   and   (7, 4)   are on the graph  of f(x)

 

The inverse reverses these....so.....the points   ( 2, 1) , ( 3, 4)  and  (4, 7)   are on the inverse

 

f-1(3)  =   4

 

So

 

f-1  ( f-1 (3)) =  f-1(4)   =    7

 

 

cool cool cool

 Dec 19, 2019

16 Online Users

avatar